Comparative ABO blood group and rhesus factor distribution between homogenous and heterogenous populations in South Eastern Nigeria - Onah, Ikechukwu Eugene; Moses, Ezinne Veronica; Ugwuoke, Ifeyinwa Esther; Eze, Sabina Chioma; Okwor, Jude Ifeanyichukwu; Ubachukwu, Patience Obiageli (Asian Journal of Medical Sciences, 2019)
Background: The ABO blood group and Rhesus (Rh) factor remain the most important blood group in transfusion medicine. Knowledge of ABO and rhesus blood group distribution within a population is indispensable for transfusion medicine, clinical and marriage counselling. Aims and Objectives: The objectives of this study were to provide data and compare the pattern of ABO and rhesus blood group distribution between a homogenous and a heterogenous population. Material and Methods: Blood was collected from 352 University students representing a heterogenous population and 235 primary school pupils in a local community representing homogenous population. The ABO and rhesus blood groups were determined using white tile and agglutination methods. Results: Among the 352 and 235 individuals studied in UNN and HFNP, blood groups O had the highest frequency with 54.80% and 51.06% respectively while blood group AB had the least frequency of 4.50% and 3.40% in UNN and HFNP respectively. Rhesus positive had the highest frequency of 88.63% and 95.33% while rhesus negative had the frequencies of 11.35% and 4.68% in UNN and HFNP respectively. Rhesus negative was highest among females in UNN 26 (7.37%) while males had the highest rhesus negative 7 (2.98%) in HFNP. In both study populations, there was no significant difference in ABO and rhesus blood group distribution between the males and females (P > 0.05). Conclusions: A homogenous population is associated with low prevalence of rhesus negative compared to a heterogenous population.